La desnutrición infantil en la comunidad wichí y sus representaciones sociales: un abordaje desde la teoría de los campos de Bourdieu - Costas Czarnescki, María Paula (2024)
Objective: To explore the social representations (SRs) of child malnutrition among fathers, mothers orguardians of the Wichí indigenous community and healthcare professionals from the General José de SanMartín department, Salta, using Pierre Bourdieu’s field theory (FT). Materials and methods: A qualitative study was conducted within a social–critical and interpretive paradigm of SRs. Participant observation, in-depth interviews and focus groups were employed to collect data from healthcare professionals and Wichí mothers with malnourished children from the General José de San Martín department, Salta, until data theoretical saturation and intramethod triangulation were achieved. The analysis was based on Pierre Bourdieu’s FT, using the categories proposed by the author. The study variables sought to understand the health field (HF) in a holistic, multidimensional and qualitative way. Results: In the HF, inequalities were observed in the dispositions of social agents according to the capitals at stake. For healthcare professionals, economic capital, understood as “institutional resources and assets,” was considered the most important form of capital, while for the Wichí community, the focus was on “economic capital in relation to cultural capital” (self-sustainability and respect for their culture).Efforts to reduce these inequalities created ongoing tension and social pressure. Disagreements were also observed among SRs of child malnutrition, particularly concerning health indicators versus intercultural care, the Wichí language and worldview versus the Spanish language, the hegemonic biomedical approach versus ecological and intercultural perspectives, community support based on welfare versus community support based on respect for the Wichí culture, along with other actions decontextualized from the reality of theregion. Conclusions: Given the existing disagreements and inequalities between healthcare professionals and the Wichí community, it isrecommended to promote ways of being, doing and thinking in the intercultural and contextualized training approaches for healthcareprofessionals. This would enable more effective responses to child malnutrition in the indigenous communities of Salta.